(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
Using literature and newspapers as materials for teaching culture provides learners with authentic insights into the values, traditions, and everyday life of a society; while literature teaches cultural and emotional interests through stories and characters, newspapers uncover learners to real-time events, language usage, and societal issues, making them both essential tools in culturally enriched language education.